Symbolism in Boho Oi Ndeu, A Marriage Ritual of Dou Donggo - Subari, Subari (Komunitas, 2018)
This research was about the meanings of symbols in ‘Boho Oi Ndeu’, a marriage ritual of Dou Donggo. It was conducted in Dou Donggo Communities as a sample. This study was conducted by using the ethnography survey. The writer has been living in Dou Donggo Community since he was born. The method used was interview by  collecting the data from primary and secondary sources. The results of the research shows that there were a lot of symbols meaning in ‘Dou Donggo Marriage’ ritual ceremony which many people did not know before. So the Dou Donggo Marriage ritul ceremony should be protected as a cultural heritage of dou donggo which enrich the national cultural treasures of our country, Indonesia.